Effect of previous Chlamydia Trachomatis infection on the outcomes of ivf/icsi treatment: a retrospective study - Dan Zhang; Zengyan Wang; Xingyuan Hu; Chunguang Ma; Yuanlin Ma; Yanwen Xu (BMC, 2022)
Abstract Background The impact of Chlamydia trachomatis infection (CT) on the outcomes of In-Vitro Fertilization / Intracytoplasmic sperm injection (IVF/ICSI) has been controversial. Methods A total of 431 infertility women aged 20-38 years with or without Chlamydia trachomatis infection before fresh/ frozen embryo transfer were included to investigate the effect of cured CT infection. The infected group was divided into two subgroups for ≤3 months and > 3 months according to the different intervals between Chlamydia trachomatis positive testing and embryo transfer. The effect of chlamydia infection and the intervals between infection and embryo transfer on pregnancy outcomes was analyzed with correction for potential confounders within a multivariable model. Results Our results revealed that implantation rate was significantly lower and the premature rupture of membranes (PROM) was higher in women with CT infection than non-infection. The multivariate logistic regression analysis adjusting for baseline characteristics showed no significant difference in live birth rate between neither two groups nor two subgroups. Conclusions The study suggests that previous Chlamydia trachomatis infection would lead to high risk of PROM. The intervals between infection and embryo transfer would not impact the pregnancy outcomes of IVF/ICSI.